Altered serum interleukin-4 and monocyte chemoattractant protein-3 levels are associated with generalized anxiety disorder: a case-control study - Most. Humayra Binta Rashid; Mehedi Islam; Sardar Mohammad Ashraful Islam; Md. Rabiul Islam (Experimental Biology and Medicine, 2026)
Generalized Anxiety Disorder (GAD) is a long-term mental health condition often associated with immune system dysregulation. While pro-inflammatory and anti-inflammatory cytokines are known to influence neuroinflammation, their specific roles in GAD remain less understood. This study investigates the relationship between serum levels of IL-4 and MCP-3 and GAD in a Bangladeshi population. This case-control study included 44 patients with GAD and 44 healthy controls (HCs). Participants were examined using the GAD-7 scale. Serum IL-4 and MCP-3 levels were measured using ELISA. Data were analyzed using t-tests, Spearman’s correlation, and Receiver Operating Characteristic (ROC) curve analysis to assess diagnostic performance. GAD patients had significantly lower serum IL-4 levels (11.82 ± 10.91 pg/mL) and higher MCP-3 levels (57.80 ± 19.85 pg/mL) compared to HCs (IL-4: 24.51 ± 15.36 pg/mL; MCP-3: 34.01 ± 15.75 pg/mL; p < 0.001). IL-4 levels showed a significant negative correlation with GAD-7 scores (r = −0.496, p < 0.001), while MCP-3 showed a positive correlation (r = 0.544, p < 0.001). ROC analysis indicated that MCP-3 had higher diagnostic accuracy (AUC = 0.848, sensitivity = 87.6%, specificity = 84.3%) compared to IL-4 (AUC = 0.782, sensitivity = 80.2%, specificity = 78.5%). Moreover, decreased IL-4 and elevated MCP-3 levels were found to be significantly associated with GAD severity, suggesting an immune imbalance. These cytokines may serve as promising diagnostic biomarkers and therapeutic targets for GAD. Further longitudinal studies are recommended to investigate this causal relationship and its underlying mechanisms.